The inhibitor of volume‐regulated anion channels DCPIB activates TREK potassium channels in cultured astrocytes. (20th February 2013) - Minieri, L; Pivonkova, H; Caprini, M; Harantova, L; Anderova, M; Ferroni, S
<x xml:space="preserve">Abstract</x> Background and Purpose The ethacrynic acid derivative, 4‐(2‐butyl‐6, 7‐dichlor‐2‐cyclopentylindan‐1‐on‐5‐yl) oxobutyric acid (DCPIB) is considered to be a specific and potent inhibitor of volume‐regulated anion channels (VRACs). In the CNS, DCPIB was shown to be neuroprotective through mechanisms principally associated to its action on VRACs. We hypothesized that DCPIB could also regulate the activity of other astroglial channels involved in cell volume homeostasis. Experimental Approach Experiments were performed in rat cortical astrocytes in primary culture and in hippocampal astrocytes in situ. The effect of DCPIB was evaluated by patch‐clamp electrophysiology and immunocytochemical techniques. Results were verified by comparative analysis with recombinant channels expressed in COS‐7 cells. Key Results In cultured astrocytes, DCPIB promoted the activation of a K+ conductance mediated by two‐pore‐domain K+ (K2P) channels. The DCPIB effect occluded that of arachidonic acid, which activates K2P channels K2P 2.1 (TREK‐1) and K2P 10.1 (TREK‐2) in cultured astrocytes. Immunocytochemical analysis suggests that cultured astrocytes express K2P 2.1 and K2P 10.1 proteins. Moreover, DCPIB opened recombinant K2P 2.1 and K2P 10.1 expressed in heterologous system. In brain slices, DCPIB did not augment the large background K+ conductance in hippocampal astrocytes, but caused an increment in basal K+ current of neurons. Conclusion and Implications Our results indicate that the neuroprotective effect of DCPIB could be due, at least in part, to activation of TREK channels. DCPIB could be used as template to build new pharmacological tools able to increase background K+ conductance in astroglia and neuronal cells.